Ninety days transplant free survival with high volume plasma exchange in Wilson disease presenting as acute liver failure. Issue 1 (28th December 2020) - Pawaria, Arti; Sood, Vikrant; Lal, Bikrant Bihari; Khanna, Rajeev; Bajpai, Meenu; Alam, Seema
Abstract: Objective: To study the efficacy and safety of high volume plasma exchange (HVPE) in Wilson disease presenting as acute liver failure (WD‐ALF). Methods: An analysis of prospectively collected data of consecutively admitted WD‐ALF cases was done and patients were divided into two groups: (i) high volume plasma exchange (HVPE) group‐ who received HVPE + standard medical therapy (SMT), and (ii) SMT group‐ received only SMT. Outcome measure was transplant free survival (TFS) at 90 days post enrollment, change in biochemical, hemodynamic parameters & incidence of organ dysfunction in HVPE as compared to SMT group, and HVPE related complications. Results: Out of the total 43 cases of WD‐ALF reported in the study period, 37 were enrolled (median age 9 years, 62.2% males). All biochemical parameters and prognostic indices except blood ammonia and serum creatinine improved significantly at 72 to 96 hours after enrollment in the HVPE group. Overall, TFS at 90 days was present in 9/19 (47.3%) in HVPE group vs 3/18 (16.6%) in the SMT group (OR 2.84, 95% CI 0.91‐8.8, P = .049). Kaplan Meier survival analysis revealed that HVPE group had significantly higher cumulative survival as per the Log Rank test ( P = .027); median days of survival was 38 days (IQR 12‐63) in HVPE group vs 14 (IQR 5‐22) days in SMT group. Conclusions: The present study indicates that in children with WD‐ALF, HVPE not only acts as a bridging therapy to LT but may also improve proportion of the cases with TFS.